(NmASTER I mARGARITA(B: [(NrOMAN(B] / s - (NbULGAKOW(B, (NmIHAIL aFANASXEWI^s ((NmOSKWA(B: s (NsOWREMENNIK(B, s, 1986)
(NrOMAN(B, (NSOZDAWAW[IJSQ PISATELEM W TE^ENIE MNOGIH LET(B, (NPOSWQ]EN OB]E^ELOWE^ESKIM WOPROSAM VIZNI(B, (NSMERTI(B, (NL@BWI(B, (NKRASOTY(B.s
rus
Keywords: (NfILOSOFSKIJ ROMANs